2010
DOI: 10.3109/09513590.2010.540601
|View full text |Cite
|
Sign up to set email alerts
|

Is sildenafil citrate affect endometrial receptivity? an immunohistochemical study

Abstract: The authors aimed to investigate the effect of sildenafil citrate (Sc) on expressions of β(3) integrin and vascular endothelial growth factor (VEGF), which is taking part in endometrium receptivity in implantation window period in controlled ovarian hyperstimulation (COH) performed rats. In this study, Wistar albino female rats were used and were divided into four groups as control, COH, Sc, and COH + Sc groups. They were sacrificed on the third, fourth, and fifth day of pregnancy, uteruses were resected, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
0
17
0
1
Order By: Relevance
“…Sildenafil has been shown in animal studies to significantly reduce elevated sFLT1 and sENG, increase free VEGF, and reverse oxidative stress (51)(52)(53). Sildenafil treatment in pre-eclamptic rat studies has lowered blood pressure, reduced proteinuria, and enhanced placental perfusion (52).…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil has been shown in animal studies to significantly reduce elevated sFLT1 and sENG, increase free VEGF, and reverse oxidative stress (51)(52)(53). Sildenafil treatment in pre-eclamptic rat studies has lowered blood pressure, reduced proteinuria, and enhanced placental perfusion (52).…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil citrate was shown to have selective endometrial vasodilatory action in women with Asherman syndrome [26] and improves endometrial development in women with thin endometrium by increasing radial artery flow [27] . In addition, animal studies showed that sildenafil citrate modulates endometrial receptivity by affecting endometrial VEGF and β3 integrin expression during implantation window [28] . Moreover, sildenafil citrate was shown to have an immunomodulatory effect on the peri-implantation endometrial microenvironment by inhibiting NK-cell activity [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil citrate is a phosphodiesterase-5 inhibitor that enhances subendometrial blood flow by potentiating the vasodilatory effect of nitric oxide [6] . It was reported to improve uterine blood flow, enhance endometrial development [7][8][9][10] and modulate endometrial receptivity [11] . Thus, it was used with varying success in the setting of repeated IVF failure with poor endometrial development [8] and to lesser extent in the setting of clomiphene citrateinduced thin endometrium [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Имеются также клинико-экспериментальные доказательства эффективности и безопасности применения силденафила при лечении репродуктивных нарушений у женщин (синдром «тонкого эндометрия»), воспалительных гинекологических заболеваний и их последствий [91][92][93], а также женских сексуальных дисфункций, в т. ч. медикаментозно-индуцированного генеза [94][95].…”
Section: применение силденафила в акушерстве и гинекологииunclassified